Effectiveness of Environmental Exploration Learning (Jas) Approach Assisted by Education Card - Malinda, Annisa Lintang; HB, F Putut Marin; Rahayuningsih, Margareta (Journal of Biology Education, 2017)
This study would analyze the effectiveness of JAS learning with media education card of biodiversity onbiology learning outcome of students at SMAN 1 Limbangan. This is a Quasi-Experimental study byNonequivalent Control Group Design. The population in this study were six classes’ students of grade Xin the odd semester of 2016/2017 academic year. The sample was taken by purposive sampling, X 5 andX 6 as experimental classes and X 2 as the control class. The results of the analysis showed the average ofcognitive learning outcomes in experimental class is 85,42 with learning completeness of 91,89%, whilethe control class is 70.7 with learning completeness of 26.47%. Psychomotor learning outcome ofexperimental classes is 82,43. Affective learning outcome of the experimental class is 74,32. In general,teachers and students also responded very well to apply learning. This study concludes that the NaturalExploration Learning (Jelajah Alam sekitar / JAS, Indonesia) model with the education card is effectivefor learning outcomes of students at SMAN 1 Limbangan.